The paradox of Ukrainian Lviv : a borderland city between Stalinists, Nazis, and nationalists - Amar, Tarik Youssef Cyril, 1969- (Cornell University Press, 2015)
"This book is a local and transnational study of the twentieth-century experience of a Central European borderland city with four key forces of European and global twentieth-century history: Soviet Communism, Soviet nation-shaping (here, Ukrainization), nationalism, and Nazism. It examines a fundamental layer in the making of modern Lviv by focusing on its World-War-Two and postwar transformation from an important multi-ethnic city (formerly known, mostly, as Lwów and Lemberg) into a Soviet and Ukrainian urban center"--